Effect of Low Dose (100mg/kg) of Zinc Telluride (ZnTe) on Hematology of Male Albino Mice (Mus musculus) - Muhammad Khalid, Zeenat Zafar, Nisar Ahmad, Sheikh Muhammad Azam, Irish Atiq, Ahmad Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: ZnONPs have been identified from a variety of perspectives, including organic chemistry and toxicology, and under these circumstances, they were deemed to be among the most lethal nanoparticles. The aim of present study to access the effect of low dose (Zinc Telluride) on hematology of Male Albino Mice. Method: Experiment was conducted for fifteen days and oral suspension of ZnTe (Zinc Telluride) was applied orally in the suspension form to male albino mice (Mus musculus). Two groups were devised as Treated and Control. Each group consisting of three treatment organisms. Two sample t-test was applied to evaluate the effects of ZnTe low dose (100mg/Kg) on albino mice (Mus musculus) hematocrit. Results: Results revealed that the number of WBC, GRA and LYM increased non-significantly (p=0.50, 0.46 and 0.44 respectively) while MON decreased non-significantly (p = 0.42). The number of LYM% MON% and GRA% decreased non-significantly (p = 0.52, 0.54 and 0.41 respectively) as compared to the control group (Table1 and 2). While our results depicted that the number of RBC% decreased highly significantly (p=0.0071) in treated animals but HCB and HCT decreased highly significantly (p = 0.0022 and 0.0028 respectively) in treated group as compare to the control group. Results observed for MCV MCH and PCT decreased non-significantly (p=0.060, 0.13 and 0.054 respectively) as compare to the control group. While number of MCHC, RDW-SD MPV and PDW increased non-significantly (p=0.50, 0.79, 0.18 and 0.16) in treated animals. Conclusion: It was also observed that there was no differences in weight gain in both control and treated group animals found. Further research is required to evaluate the long term effects of ZnTe on mammals and to investigate their remedies. Keywords: ZnONPs, ZnTe, Hematology, Male Albino Mice